Perilaku Masyarakat dalam Pelaksanaan Protokol Kesehatan sebagai Upaya Pencegahan Covid-19 di Punggawan, Banjarsari Surakarta - Rasmaya Niruri; Yeni Farida; Fea Prihapsara; Adi Yugatama; Siti Ma'rufah (Pharmacon: Jurnal Farmasi Indonesia, 2021)
The Covid-19 infection has spread to almost all regions of Indonesia. The government has issued a health protocol policy for the public in carrying out their activities to minimize the transmission of covid-19. This study aimed to obtain an overview of public compliance behavior in implementing health protocols as an effort to prevent Covid-19. The questionnaire survey was conducted at one of the pharmacies in the Banjarsari area of Surakarta for the period 14-30 September 2020. The research subjects were determined by purposive sampling method. The questionnaire contains 16 statement items covering the domain of social distancing, use of masks, maintaining hygiene and hand washing, and cough etiquette. Respondent behavior was classified into 2 categories, namely compliance and noncompliance. Respondent characteristic data (gender, age, and occupation) were tested for their relationship with compliance behavior. This study involved 54 respondents who were dominated by women (68.52%), age range 36- 45 years (37.18%), and work as private employees (37.04%). A study on 54 respondents showed that 51.85% of respondents had complied with the implementation of health protocols. Community non-compliance was still high in the domain of maintaining hygiene and cough etiquette. Gender, age, and occupation were not significantly related to respondent behavior.